The Triglyceride-Glucose Index is Associated with Vitamin D Status in Metabolic-Associated Fatty Liver Disease - Liu Z; Zhang W; Zhao Z; Li W; Zhang J (Diabetes, Metabolic Syndrome and Obesity, 2023)
Zhiping Liu, Wensha Zhang, Zhiwei Zhao, Wenhao Li, Jinhua Zhang Department of Gastroenterology, Hankou Hospital of Wuhan, Wuhan, Hubei, People’s Republic of ChinaCorrespondence: Jinhua Zhang, Department of Gastroenterology, Hankou Hospital of Wuhan, No. 7, Erqice Road, Jiangan District, Wuhan, Hubei, 430012, People’s Republic of China, Tel +86 27 8228 3181, Email jinhuazh2000@outlook.comPurpose: Vitamin D deficiency was thought to be associated with insulin resistance and metabolic-associated fatty liver disease (MAFLD). The aim of this study was to investigate the relationship between the triglyceride-glucose (TyG) index, a useful surrogate biomarker of insulin resistance, and vitamin D status in patients with MAFLD.Patients and Methods: A total of 566 patients with MAFLD were included in this retrospective cross-sectional study. Clinical characteristics were compared between participants with and without vitamin D deficiency. The association between the TyG index and serum 25-hydroxyvitamin D [25(OH)D] levels was determined by Spearman correlation analysis and logistic regression analysis. The receiver operating characteristic curve (ROC) was used to assess the diagnostic efficacy of TyG index for vitamin D deficiency in MAFLD patients.Results: The TyG index levels were higher in the vitamin D deficient group than in the non-vitamin D deficient group, and serum 25(OH)D was negatively correlated with the TyG index. The TyG index was an independent risk factor for vitamin D deficiency in patients with MAFLD. The area under the curve (AUC) of the TyG index for the identification of vitamin D deficiency in MAFLD patients was 0.744 (95% CI: 0.701– 0.787, p< 0.001).Conclusion: The TyG index is negatively associated with vitamin D status in patients with MAFLD. In patients with MAFLD, a higher TyG index may be an indication of a higher prevalence of vitamin D deficiency.Keywords: triglyceride-glucose index, 25-hydroxyvitamin D, metabolic-associated fatty liver disease, insulin resistance